The Relationship Between Adversity Quotient and Learning Outcomes of Nursing Students - Cucu Rokayah; Senny Apriliani; Tri Nur Jayanti (Indonesian Journal of Global Health Research, 2023)
The effectiveness of student learning can be determined by learning outcomes. Good learning outcomes are not easily attained, ther are numerous obstacles and challenges to overcomes. Not all pupils are capapble of overcoming obstacle and challenges in order to achieves positive learning outcomes. The intelegence required to overcome learning obstacle is adversity quotient. This study aims to determine the relationship between Adversity Quotient and Learning Outcomes of Nursing Student. This Research uses quantitative research, with a descriptive correlation approach (Cross sectional). Population in this study is 494 nursing students, and sample 221 students with stratified random sampling technique. Data collection techniques using the Adversity Response Profile questionnaire. Data analysis used frequency distribution and Product Moment correlation test. The results showed that 98% of the Adversity Quotient of Nursing Students were in the moderate AQ category (Camper). Nursing student learning outcomes 21% are in the very bright category. Correlation test obtained p value 0.009 (<0.05), there is a relationship between Adversity Quotient with nursing student learning outcomes with a correlation coefficient of 0.176 which has a very weak relationship level with a positive direction. Based on the results of the study.